A Transposição Didádica dos Gêneros do domínio do discursivo publicitários nos livros didáticos - Lima, Sandra Maria Alves de (2012)
Advertising text has been a subject of many investigations, because of its multimodal universe. Embodied by a linguistic and discursive materiality laying on scene persuasion, argumentation and power imagery of multissemiotics elements, the advertising text acts as an instrument of power, creating and destroying, promising and denying (CARVALHO, 2007). Advertising not only invites us to act for it, but directs us to look at it. It was under this moving look - of charm and interrogations - that discussions raised in this research were born. Investigations are directed to the school environment, in special, for the discursive advertising domain in Portuguese Language Textbook. It is from this environment that was born our research whose main objective is to analyze how does the didactic transposition of textual genres, described by Marcuschi (2008) as belonging to the "advertising" discourse domain (focusing on advertising genre) in didactic books teaching Portuguese Language before and after the advent of the PCN. Textbooks taken as reference for the study are historically situated in the 90s of the twentieth century and 10 century. Such books refer to elected 7th and 8th grades, currently corresponding to the 8th and 9th grades of elementary school. The choice is justified by the fact that in these Textbook teaching series the presence of advertising domain is recurrent and "didactized". In addition, we are also concerned in analyzing books that circulated around us and our regional reality. Hence, we elected books that were used by two public high schools: Municipal School Clementina Ana da Conceição in Jaçanã city in the Rio Grande do Norte state, State School for Elementary and High school Carlota Barreira in Areia city, Paraíba state. In our research the following categories of analysis were highlighted: (1) presence of advertising in DB, (2) fluctuation terminology: concepts and classifications; (3) The complexity of concepts facilitation, (4) what they propagate, and from which nature are the explored advertisements. From our analysis, we observe how the treatment of textual "advertising" genres have been inserted into Textbooks, and how occurs, in general, their didactic transposition. Focusing on the issue of fluctuating terminology, we noted the difficulty in drawing boundaries between the genres of advertising domain in the Textbooks. However, this also would result in the complexity - in the field of scientific knowledge - of delimiting genres of the same domain. To accomplish our studies, it was required a thorough and systematic dialogue with theories regarding the concept of "Didactic Transposition", due to the theoretical Chevallard Yves (1991), research on the textual genres - Bezerra (2005), Marcuschi (2008), Bazerman (2005), Swales (2004), among others - and studies involving the field of "Advertising" - Sandmann (2002), Carvalho (2007) and others